The Advantage of Incumbents in Coalitional Bargaining - Jaakko Meriläinen; Janne Tukiainen (Aboa Centre for Economics (ACE), 2021)
The composition of governing coalitions does not always reflect the relative sizes of the coalition members, but research has not been able to fully reconcile why. We propose that political parties with more (reelected) incumbent representatives fare better in coalitional bargaining. To evaluate this argument empirically, we construct a data set of parties and governing coalitions in Finnish local governments. Using an instrumental variable strategy that hinges on within-party close elections between incumbents and non-incumbents, we find that, ceteris paribus, having more re-elected incumbents improves a party s coalitional bargaining outcomes. Descriptive evidence suggests that incumbent representation is particularly useful when a party is in a disadvantaged position (e.g., it is ideologically distant from other parties) and when the bargaining environment is more complex (e.g., there are more parties). Lastly, incumbent representation also matters for selection: parties that have more incumbent representatives nominate more incumbents in the municipal executive.
Keywords: C26; D72; 330; coalitional bargaining; coalitions; government formation; incumbency advantage; local government; multi-party system